Optimalisasi Pengembangan Pertanian Modern melalui Program ”Ngariung Tani” (Studi Kasus: Desa Sindangsari, Kecamatan Ciranjang, Kabupaten Cianjur) - Amelia Paramitha Mahanani; Lailatul Qodriyah Agne Verawati; Ni Made Armini Wiendi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Currently the development of the concept of modern agriculture that is used combines two concepts, namely optimization of agricultural production through improving technology and improving the quality of crop yields using the latest technology that reflects the modernity in the agricultural world. "Ngariung Tani" is carried out by means of discussion between farmers and students, and PPL as an intermediary between students and farmers. This activity aims to discuss issues of agriculture and agricultural cultivation in the village of Sindangsari where most people earn a living as farmers. The increasing insight of students about the practice of rice cultivation and problems, especially those in the village of Sindangsari and the increasing insight of farmers about the modern agricultural system is an indicator of the success of discussion activities in community service. Keywords: agriculture, cultivation, Sindangsari, technology